Haben Otto Neugebauer und William Feller die Niljahre richtig gemittelt? - Krauss, Rolf (Zeitschrift für ägyptische Sprache und Altertumskunde, 2017)
Neugebauer critized Meyer’s hypothesis that the 365-day calendar resulted from observation of the heliacal risings of Sothis, maintaining that astronomical observation should have resulted in a year of 365.25 days. Instead, Neugebauer traced the 365-day calendar back to a Nile year based on computational equalization of varying successive intervals between minimum or maximum gauge readings. He did not propose the anachronistic calculation of the arithmetic average but alluded instead to a procedure using stroke marks allegedly resulting in years of 365 full days, while neglecting the quarter-day. Neugebauer and his collaborator Feller overlooked the fact that four successive years of 365.25 days equal 1461 full days and that the sums of numerous successive intervals between the same gauge values fractionize into multiples of Nile years of 365 and 366 full days. Thus, a revised analysis of long-term Nile year statistics produces the same results as a short-term observation of the heliacal risings of Sirius.